2015
DOI: 10.3390/genes6010124
|View full text |Cite
|
Sign up to set email alerts
|

RNA Export through the NPC in Eukaryotes

Abstract: In eukaryotic cells, RNAs are transcribed in the nucleus and exported to the cytoplasm through the nuclear pore complex. The RNA molecules that are exported from the nucleus into the cytoplasm include messenger RNAs (mRNAs), ribosomal RNAs (rRNAs), transfer RNAs (tRNAs), small nuclear RNAs (snRNAs), micro RNAs (miRNAs), and viral mRNAs. Each RNA is transported by a specific nuclear export receptor. It is believed that most of the mRNAs are exported by Nxf1 (Mex67 in yeast), whereas rRNAs, snRNAs, and a certain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
111
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(114 citation statements)
references
References 192 publications
(223 reference statements)
3
111
0
Order By: Relevance
“…2). This would be expected because, in addition to its role in mRNA stabilization, HuR is necessary for the export of adenine-and uridine-rich element-containing mRNAs from the nucleus to the cytosol (67,68). Our finding that HuR was bound directly to Slc7a11 mRNA in the polysomal fraction of the cytosol and that this was dependent on IL-1␤ strengthens this conclusion (Fig.…”
Section: Discussionsupporting
confidence: 76%
“…2). This would be expected because, in addition to its role in mRNA stabilization, HuR is necessary for the export of adenine-and uridine-rich element-containing mRNAs from the nucleus to the cytosol (67,68). Our finding that HuR was bound directly to Slc7a11 mRNA in the polysomal fraction of the cytosol and that this was dependent on IL-1␤ strengthens this conclusion (Fig.…”
Section: Discussionsupporting
confidence: 76%
“…This suggests that unlike in opisthokonts and plants, GTP and not ATP powers mRNA export in trypanosomes. Interestingly, non protein coding RNA in opisthokonts, such as tRNAs, small nuclear RNAs, micro RNAs and preribosomal subunits, are exported out of the nucleus on a Ran gradient by karyopherins, similar to protein export (reviewed in 47,56 ). Additionally, a small subset of mRNA export is dependent on the karyopherin, Exportin 1 (Crm1).…”
Section: Tms and Alps: Multiple Ways To Tether A Leviathanmentioning
confidence: 99%
“…Recent structural studies have revealed aspects of the mechanisms employed by transport receptors to enable specific cargo recognition, and genome-wide approaches have provided the first insights into the diverse composition of pre-mRNPs during export. Furthermore, the regulation of RNA/RNP export is emerging as an important means to modulate gene expression in stress conditions and disease.The compartmentalisation of eukaryotic cells into nucleus and cytoplasm allows the spatial separation of different steps in gene expression into nuclear events such as transcription, RNA processing and splicing, and cytoplasmic translation [1,2]. However, such separation necessitates the nucleocytoplasmic transport of various biogenesis intermediates, mature RNAs and ribonucleoprotein complexes (RNPs), including messenger (m)RNPs, transfer (t)RNAs, small nuclear (sn)RNPs, micro (mi)RNPs and ribosomal subunits, which are transported as precursors during their biogenesis or in their mature form.…”
mentioning
confidence: 99%
“…The compartmentalisation of eukaryotic cells into nucleus and cytoplasm allows the spatial separation of different steps in gene expression into nuclear events such as transcription, RNA processing and splicing, and cytoplasmic translation [1,2]. However, such separation necessitates the nucleocytoplasmic transport of various biogenesis intermediates, mature RNAs and ribonucleoprotein complexes (RNPs), including messenger (m)RNPs, transfer (t)RNAs, small nuclear (sn)RNPs, micro (mi)RNPs and ribosomal subunits, which are transported as precursors during their biogenesis or in their mature form.…”
mentioning
confidence: 99%